The Influence of Nutritional Knowledge and Food Choice Attitudes on the Eating Behavior of Adolescents in Kediri District - Hadi, Stifani Dianisa Prafita; Soeyono, Rahayu Dewi; Sutiadiningsih, Any; Miranti, Mauren Gita (Universitas Pendidikan Indonesia (UPI), 2024)
This study investigates the impact of nutritional knowledge and food choice attitudes on adolescent eating behavior. A total of 77 people aged 12-21 years were surveyed using purposive sampling in Kediri Regency, East Java. The research design was observational with a cross-sectional approach. The results showed that 67.53% of teenagers were female and 32.47% were male. 50.65% of teenagers had good nutritional knowledge, 64.94% had adequate attitudes towards food choice, and 61.04% had adequate eating behavior. The correlation test showed no significant relationship between nutritional knowledge and attitudes towards food choice, while the correlation test showed a significant relationship between nutritional knowledge and adolescent eating behavior and food choice attitudes and eating behavior. A multiple correlation value (R) of 0.005 was obtained, indicating that there is an influence between nutritional knowledge and attitudes towards food choices on eating behavior in adolescents.